2022
DOI: 10.1186/s12891-022-05878-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphological differences in scoliosis curvatures as a cause of difficulties in its early detection based on angle of trunk inclination

Abstract: Introduction The three dimensional deformation of the spine in scoliosis is specific for a given child with regard to the number and length of curvatures, their degree of rotation and the size of the curvature angle. Early diagnosis of scoliosis in a clinical examination according to the Adams test depends on the correlation between the angle of trunk inclination (ATI) and the Cobb angle and the adopted diagnosis criterion. The aim of the study was to demonstrate the need to adopt different dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has been demonstrated that relying solely on the criterion of the trunk rotation angle (ATR) for predicting the development of back asymmetry may lead to significant errors [ 12 , 13 , 14 ]. To enhance the diagnosis and effectiveness of conservative treatment for IS, the authors propose considering two aspects in conservative IS treatment based on reports in the field of scoliosis pathomorphology and etiopathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that relying solely on the criterion of the trunk rotation angle (ATR) for predicting the development of back asymmetry may lead to significant errors [ 12 , 13 , 14 ]. To enhance the diagnosis and effectiveness of conservative treatment for IS, the authors propose considering two aspects in conservative IS treatment based on reports in the field of scoliosis pathomorphology and etiopathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, they suggest lowering the ATR threshold for qualifying for PSSEs in younger children aged 6–12 years. Reports indicate that more than half of children with an ATR of 5–6° may have scoliosis with a Cobb’s angle of 15° in the lumbar or thoracolumbar region [ 13 , 14 ]. Burwell and Park referred to this period in a child’s life as the pre-scoliotic period, which typically precedes the sudden onset of scoliosis during puberty by several months and is characterized by slight trunk asymmetry, often accompanied by other postural disorders [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation